2006
DOI: 10.1198/016214505000001168
|View full text |Cite
|
Sign up to set email alerts
|

How Many People Do You Know in Prison?

Abstract: BIBLID [1130-2887 (2013) 65, Fecha de recepción: 1 de julio del 2013 Fecha de aceptación: 18 de octubre del 2013 RESUMEN: Este artículo propone un nuevo método comparado para el estudio de los vínculos entre los partidos políticos y los electores. Visto desde los electores, la principal distinción entre los partidos clientelares y los programáticos se encuentra en el modo de acceso a los beneficios públicos. En el primer caso, partidos clientelares, las redes partidarias median en el acceso a los beneficios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(77 citation statements)
references
References 10 publications
2
63
1
6
Order By: Relevance
“…Previous research has suggested methods to adjust for recall bias based on the relationship between respondents’ recalled ties and the sizes of known groups of interest (Killworth et al 2003; Zheng et al 2006; McCormick and Zheng 2007; McCormick et al 2010). Our exploratory work suggests a linear relationship between the two on the log scale.…”
Section: Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has suggested methods to adjust for recall bias based on the relationship between respondents’ recalled ties and the sizes of known groups of interest (Killworth et al 2003; Zheng et al 2006; McCormick and Zheng 2007; McCormick et al 2010). Our exploratory work suggests a linear relationship between the two on the log scale.…”
Section: Modelsmentioning
confidence: 99%
“…These questions are widely used on surveys such as the General Social Survey to measure connectivity patterns between individuals. Statistical work in this area includes Zheng et al (2006) who used aggregated relational data to estimate social structure through overdispersion, McCormick et al (2010) who developed methods for estimating individuals’ personal network size and rates of mixing between groups in the population, and McCormick and Zheng (2012) who estimated the demographic composition of hard-to-reach populations. While we focus here on estimating the sizes of population groups, the previous work focused primarily on estimating features of the population social network and the dynamics of interactions between population groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater variation between individuals in their number of contacts has been proposed as a measure of clustering in the underlying network (Zheng et al, 2006), which shows some promise as a means of obtaining social network information (Drumright and Frost, 2010). However, like all self-reported information, it is subject to numerous errors, and it remains to be seen whether additional information, for example on the psychology of estimation, could be used to improve accuracy.…”
Section: Social Network Sizementioning
confidence: 99%